Green low-carbon machine-made sand terrace concrete and preparation method thereof
By adding specific ratio expansion agents, curing agents and other components to the cement floor materials, the shrinkage and dust-free performance problems of cement floor materials are solved, and efficient shrinkage, wear and dust-resistant effects are achieved, meeting the strength requirements of C30 grade.
Patent Information
- Application Number
- CN202411993771.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
Existing cement floor materials face shrinkage problems caused by high cement usage and dust-free performance degradation caused by mineral blending.
Green and low-carbon sand floor concrete is used to improve the shrinkage, wear resistance and dust resistance of floor concrete by adding expansion agent, curing agent, cement, blending material, water, sand, gravel and water reducing agent to the concrete, and mixing evenly during the mixing process.
It achieves excellent shrinkage resistance, dust-free performance and mechanical properties, reduces the drying shrinkage rate and dust mass concentration, and meets the compressive strength requirements of C30 grade.
Smart Images

Figure CN119774972A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of building materials, and in particular to a green and low-carbon machine-made sand concrete suitable for floor applications, and in particular to a green and low-carbon machine-made sand floor concrete and a preparation method thereof. Background Art
[0002] As my country's industry continues to transform towards high-end, intelligent and refined, various technology-based manufacturing companies have put forward higher requirements for the floor performance of office spaces, production workshops and factory buildings. In modern factories, flooring has become a product that integrates high material performance requirements, high construction quality requirements and high finished product quality requirements. On the one hand, it needs to have high decorative properties to enhance the beauty of the building, and at the same time, it also needs to have functions such as flatness, wear resistance, moisture resistance and easy cleaning. Airports, parking lots, shopping malls, factory workshops, logistics warehouses and other scenes all have a large number of application requirements for high-performance flooring.
[0003] At present, the floor made of organic resin materials has good performance in dust-free, flatness, corrosion resistance, etc., but the process of this type of floor is complex, and the impact resistance, fire resistance and durability are poor. Therefore, inorganic cement-based floor materials are used in scientific and technological industrial plants, but in actual engineering applications, the existing concrete floors usually have cumbersome processes and difficult quality control. Taking the commonly used diamond abrasive floor process as an example, before its construction, it is necessary to pour a layer of fine stone concrete on the basis of structural concrete before continuing the construction of the surface layer. After the concrete surface layer is poured, it is necessary to carry out 2-3 times of sanding, compaction, and rubbing. As the concrete gradually hardens, it is necessary to continue mechanical troweling operations, and polish and shape it after curing until the strength reaches the standard. In this process, the construction period is long, the quality of the fine stone concrete layer needs to be strictly controlled, the surface layer pouring, construction process needs to be strictly controlled, and the curing process needs to be strictly controlled. Problems in any link in the entire construction process will lead to problems with the quality of the floor, which will increase other costs besides the cost of raw materials and production and transportation costs.
[0004] Therefore, this patent relies on the second phase project of A3 and B3 plots of the Gui'an Huawei Cloud Data Center High-end Park, and aims to solve the contradiction between the shrinkage problem caused by high cement consumption faced by existing cement-based floor materials and the grinding hollowing and reduced dust-free performance caused by the addition of mineral admixtures. Summary of the invention
[0005] The purpose of the present invention is to provide a green and low-carbon machine-made sand floor concrete and a preparation method thereof, so as to solve the contradiction between the shrinkage problem caused by the high cement dosage faced by cement-based floor materials in the above background and the reduction of dust-free performance caused by the addition of mineral admixtures.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] In the first aspect, the present application provides a green and low-carbon machine-made sand floor concrete; the concrete is C30 grade concrete, which is prepared using the following materials: expansion agent, curing agent, cement, admixture, water, sand, gravel and water reducer.
[0008] Furthermore, the expansion agent is a UEA expansion agent, and the main components of the UEA expansion agent are aluminum sulfate, aluminum oxide, and potassium aluminum sulfate.
[0009] Furthermore, the curing agent is a sodium silicate solution, in which SiO2 accounts for 27.3%, Na2O accounts for 8.54% and the modulus is 3.3.
[0010] Furthermore, the cement may be ordinary Portland cement, and preferably, the cement grade is 42.5.
[0011] Furthermore, the admixture may be industrial waste, preferably, the admixture may be slag or fly ash. When slag is used, its optional grade is S95. When fly ash is used, its optional grade is secondary.
[0012] Furthermore, the water comes from nature or daily water, preferably laboratory tap water.
[0013] Furthermore, the sand may be river sand, sea sand, desert sand and machine-made sand. Preferably, the sand is machine-made sand.
[0014] Furthermore, the gravel is small pieces of broken rock.
[0015] Furthermore, the water reducer is a chemical additive commonly used in concrete engineering. Preferably, the water reducer is a polycarboxylate water reducer.
[0016] In the second aspect, the present invention also discloses a method for preparing green and low-carbon machine-made sand floor concrete, which comprises the following steps: uniformly stirring cement, admixture, sand, stone, water and additives, and adding an expansion agent during the stirring process and continuing to stir uniformly, so as to improve the shrinkage resistance, wear resistance and dust resistance of the floor concrete.
[0017] Specifically, (1) cement, admixtures, sand, stone, water, water reducing agent and expansion agent are measured according to mass fraction;
[0018] (2) Put the weighed cement, admixture, sand, stone, water and water reducing agent into a mixer, and stir the mixture until it is uniform to obtain a mixture;
[0019] (3) pouring the expansion agent into the concrete mixture of step (2) during the mixing process, and continuing to mix with a mixer until it is completely uniform;
[0020] (4) The concrete mixed in step (3) is placed into a mold and vibrated.
[0021] (5) The concrete of step (4) is placed at room temperature for one day and demoulded.
[0022] (6) The demoulded test piece is placed in a constant temperature and humidity environment for curing.
[0023] (7) Apply the curing agent evenly on the surface of the cured test block to allow the substrate to absorb it. When the substrate surface becomes viscous, spray a small amount of water to promote further penetration of the curing agent. The penetration time should not be less than 10 hours.
[0024] Furthermore, the cement in step (1) may be ordinary Portland cement, preferably, the cement grade is 42.5. The admixture may be industrial waste, preferably, the admixture may be slag or fly ash. When slag is used, its optional grade is S95. When fly ash is used, its optional grade is secondary. The water comes from nature or daily water, preferably, laboratory tap water. The sand may be river sand, sea sand, desert sand and machine-made sand, preferably, the sand is machine-made sand. The gravel is small pieces of broken rock. The water reducer is a chemical additive commonly used in concrete engineering, preferably, the water reducer is a polycarboxylic acid water reducer.
[0025] Furthermore, the stirring speed in step (2) is preferably 10-16 kr / min, preferably 12.6 kr / min, and the stirring time is preferably 1-10 minutes.
[0026] Furthermore, in step (3), the stirring speed is preferably 10-16 kr / min, preferably 12.6 kr / min.
[0027] Furthermore, in step (3), the expansion agent is a UEA expansion agent, and the main components of the UEA expansion agent are aluminum sulfate, aluminum oxide, and potassium aluminum sulfate.
[0028] Furthermore, the curing temperature and humidity in step (6) are standard concrete curing conditions, i.e., temperature 20±2° C. and humidity 99% RH.
[0029] Furthermore, the curing agent in step (7) is a sodium silicate solution, in which SiO2 accounts for 27.3%, Na2O accounts for 8.54% and the modulus is 3.3.
[0030] On the third aspect, the present invention also seeks to protect the use of a green and low-carbon machine-made sand floor concrete as a floor material.
[0031] The green and low-carbon machine-made sand floor concrete with excellent anti-shrinkage and dust-proof properties is prepared by using a preparation method of the green and low-carbon machine-made sand floor concrete disclosed in the second aspect.
[0032] In a fourth aspect, the present application provides a green and low-carbon machine-made sand floor concrete; the waste glass powder low-carbon cementitious material is composed of the following raw materials: an expansion agent, a curing agent, cement, an admixture, water, sand, gravel and a water reducer.
[0033] Furthermore, the expansion agent is a UEA expansion agent, and the main components of the UEA expansion agent are aluminum sulfate, aluminum oxide, and potassium aluminum sulfate.
[0034] Furthermore, the curing agent is a sodium silicate solution, in which SiO2 accounts for 27.3%, Na2O accounts for 8.54% and the modulus is 3.3.
[0035] Furthermore, the cement may be ordinary Portland cement, and preferably, the cement grade is 42.5.
[0036] Furthermore, the admixture may be industrial waste, preferably, the admixture may be slag or fly ash. When slag is used, its optional grade is S95. When fly ash is used, its optional grade is secondary.
[0037] Furthermore, the water comes from nature or daily water, preferably laboratory tap water.
[0038] Furthermore, the sand may be river sand, sea sand, desert sand and machine-made sand. Preferably, the sand is machine-made sand.
[0039] Furthermore, the gravel is small pieces of broken rock.
[0040] Furthermore, the water reducer is a chemical additive commonly used in concrete engineering. Preferably, the water reducer is a polycarboxylate water reducer.
[0041] Beneficial effects of the present invention:
[0042] (1) The green and low-carbon machine-made sand floor concrete provided by the present invention has excellent anti-shrinkage performance, dust-free performance and mechanical properties.
[0043] (2) The green, low-carbon machine-made sand floor concrete provided by the present invention has good anti-drying shrinkage performance. The optimal shrinkage rate in 1 to 28 days is only 2 to 440 μm, which is about 50% lower than the drying shrinkage rate of ordinary concrete in 28 days.
[0044] (3) The green and low-carbon machine-made sand floor concrete provided by the present invention has good dust-free performance. The dust mass concentration generated by grinding is as low as 34.8 mg·m -3Compared with ordinary concrete, the dust mass concentration can be reduced by up to about 93.1%.
[0045] (4) The green and low-carbon machine-made sand floor concrete provided by the present invention has good compressive strength. The 28-day compressive strength is 34.8 MPa, which meets the strength requirements of concrete C30 grade. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] The present invention will be further described below in conjunction with the accompanying drawings.
[0047] Figure 1 This is a flow chart for preparing green, low-carbon machine-made sand floor concrete with excellent shrinkage resistance and dustproof performance of the present invention;
[0048] Figure 2 This is a drying shrinkage test result diagram of the green low-carbon machine-made sand floor concrete with excellent shrinkage resistance and dustproof performance of the present invention;
[0049] Figure 3 This is a test result diagram of the dust-free performance of the green, low-carbon machine-made sand floor concrete with excellent anti-shrinkage and dust-proof performance of the present invention;
[0050] Figure 4 This is a graph showing the compressive strength test results of the green, low-carbon machine-made sand floor concrete with excellent shrinkage resistance and dustproof performance of the present invention; DETAILED DESCRIPTION
[0051] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0052] Drying shrinkage test:
[0053] Comparative Example 1: This embodiment relates to a green, low-carbon machine-made sand floor concrete with excellent shrinkage resistance and dustproof performance, comprising the following steps:
[0054] The formula is calculated in parts by weight as follows: (1) 185 parts of cement; (2) 75 parts of fly ash; (3) 70 parts of slag; (4) 826 parts of sand; (5) 1031 parts of crushed stone; and (6) 7.7 parts of water reducing agent.
[0055] Among them, the cement grade is 42.5.
[0056] Wherein, the fly ash is secondary fly ash.
[0057] Wherein, the slag is S95 grade slag.
[0058] Wherein, the sand is machine-made sand.
[0059] Wherein, the crushed stone is small pieces of broken rock.
[0060] Wherein, the water reducer is a polycarboxylic acid water reducer.
[0061] The above materials are tested according to the following steps to obtain a floor concrete with excellent anti-shrinkage effect, including the following steps:
[0062] (1) Weigh the materials according to 185 parts of cement, 75 parts of fly ash, 70 parts of slag, 826 parts of sand, 1031 parts of crushed stone, and 7.7 parts of water reducer. Use an electronic balance to weigh the materials. The weighing balance accuracy of the materials is ±0.1g;
[0063] (2) Pour the weighed sand and stone from step (1) into a mixer and stir for 1 min until the mixture is uniform;
[0064] (3) Pour the weighed cement, slag and fly ash in step (1) into a mixer and stir for 1 min until the mixture is uniform;
[0065] (4) pouring the water weighed in step (1) into a blender and stirring;
[0066] (5) adding the water reducing agent weighed in step (1) into the mixer to adjust the working properties of the concrete;
[0067] (6) The mixed concrete is placed in a plastic mold and vibrated to squeeze out air bubbles.
[0068] (7) placing the concrete from step (6) indoors for one day and then demolding;
[0069] (8) Place the demoulding concrete in an environment with a room temperature of 20°C and a humidity of 50%.
[0070] (9) The shrinkage rate of concrete at different ages (1, 3, 7, 14, and 28 days) was measured using the HC-SC3 non-contact bellows shrinkage and expansion measuring instrument.
[0071] The blank case was named C-0.
[0072] Example 1: The components, mass parts and test methods of the green and low-carbon machine-made sand floor concrete with excellent anti-shrinkage and dust-proof properties involved in this example are the same as those of the blank example, except that UEA expansion agent is added in an amount of 14.8 parts.
[0073] Wherein, the expansion agent is UEA expansion agent, and the main components are aluminum sulfate, aluminum oxide and potassium aluminum sulfate.
[0074] The above materials are tested according to the following steps to obtain a green and low-carbon machine-made sand floor concrete, including the following steps:
[0075] (1) Weigh the materials according to 14.8 parts of UEA expansion agent, 185 parts of cement, 75 parts of fly ash, 70 parts of slag, 826 parts of sand, 1031 parts of crushed stone, and 7.7 parts of water reducer. Use an electronic balance to weigh the materials. The weighing balance accuracy of the materials is ±0.1g;
[0076] (2) Pour the weighed sand and stone from step (1) into a mixer and stir for 1 min until the mixture is uniform;
[0077] (3) Pour the weighed cement, slag and fly ash in step (1) into a mixer and stir for 1 min until the mixture is uniform;
[0078] (4) pouring the water weighed in step (1) into a blender and stirring;
[0079] (5) adding the water reducing agent weighed in step (1) into the mixer to adjust the working properties of the concrete;
[0080] (6) adding the UEA expansion agent weighed in step (1) into the concrete and stirring until completely dispersed;
[0081] (7) The mixed concrete is placed in a plastic mold and vibrated to squeeze out air bubbles.
[0082] (8) placing the concrete from step (7) indoors for one day and then demolding;
[0083] (9) Place the demoulding concrete in an environment with a room temperature of 20°C and a humidity of 50%.
[0084] (10) The shrinkage rate of concrete at different ages (1, 3, 7, 14, and 28 days) was measured using a HC-SC3 non-contact bellows shrinkage and expansion tester.
[0085] Example 1 is named C-U1.
[0086] Example 2: The components, mass parts and test methods of the green and low-carbon machine-made sand floor concrete with excellent anti-shrinkage and dust-proof properties involved in this example are the same as those of the blank example, and the test steps are the same as those of Example 1, except that UEA expansion agent is added in an amount of 18.5 parts.
[0087] Example 2 is named C-U2.
[0088] Example 3: The components, mass parts and test methods of the green and low-carbon machine-made sand floor concrete with excellent anti-shrinkage and dust-proof properties involved in this example are the same as those of the blank example, and the test steps are the same as those of Example 1, except that UEA expansion agent is added in an amount of 22.2 parts.
[0089] Example 3 is named C-U3.
[0090] Dust-free performance test:
[0091] Comparative Example 2: This embodiment relates to a green, low-carbon machine-made sand floor concrete with excellent shrinkage resistance and dustproof performance, comprising the following steps:
[0092] The formula is calculated in parts by weight as follows: (1) 185 parts of cement; (2) 75 parts of fly ash; (3) 70 parts of slag; (4) 826 parts of sand; (5) 1031 parts of crushed stone; and (6) 7.7 parts of water reducing agent.
[0093] Among them, the cement grade is 42.5.
[0094] Wherein, the fly ash is secondary fly ash.
[0095] Wherein, the slag is S95 grade slag.
[0096] Wherein, the sand is machine-made sand.
[0097] Wherein, the crushed stone is small pieces of broken rock.
[0098] Wherein, the water reducer is a polycarboxylic acid water reducer.
[0099] The above materials are tested according to the following steps to obtain a floor concrete with excellent anti-shrinkage effect, including the following steps:
[0100] (1) Weigh the materials according to 185 parts of cement, 75 parts of fly ash, 70 parts of slag, 826 parts of sand, 1031 parts of crushed stone, and 7.7 parts of water reducer. Use an electronic balance to weigh the materials. The weighing balance accuracy of the materials is ±0.1g;
[0101] (2) Pour the weighed sand and stone from step (1) into a mixer and stir for 1 min until the mixture is uniform;
[0102] (3) Pour the weighed cement, slag and fly ash in step (1) into a mixer and stir for 1 min until the mixture is uniform;
[0103] (4) pouring the water weighed in step (1) into a blender and stirring;
[0104] (5) adding the water reducing agent weighed in step (1) into the mixer to adjust the working properties of the concrete;
[0105] (6) The mixed concrete is placed into a plastic mold and vibrated to remove air bubbles;
[0106] (7) leaving the concrete of step (6) at room temperature for one day and demolding;
[0107] (8) The demoulded test piece is placed in a constant temperature and humidity environment for curing;
[0108] (9) The specimen was placed in a self-made test chamber and polished for 10 min. The dust-free performance was tested by the PM2.5 / PM10 detection device in the test chamber.
[0109] Furthermore, the test box described in step (8) is composed of a sealed test box, a PM2.5 / PM10 detection device and an electric roller brush. The PM2.5 / PM10 detection device is installed on the top of the box, and two electric roller brushes are placed at a height of 40 mm from the bottom of the test box, 15 mm from the side panels of the test box, and run at a speed of 200 r / min during the experiment to simulate the wear and tear of the floor concrete during actual use.
[0110] Since no expansion agent was added and no curing agent was applied in the blank example, it was named C-0.
[0111] Embodiment 4: This embodiment relates to a green low-carbon machine-made sand floor concrete with excellent shrinkage resistance and dustproof performance, comprising the following steps:
[0112] The formula is calculated in parts by mass as follows: (1) 185 parts of cement; (2) 75 parts of fly ash; (3) 70 parts of slag; (4) 826 parts of sand; (5) 1031 parts of crushed stone; (6) 7.7 parts of water reducing agent; and (7) 14.8 parts of expansion agent.
[0113] Wherein, the expansion agent is UEA expansion agent, and the main components are aluminum sulfate, aluminum oxide and potassium aluminum sulfate.
[0114] Among them, the cement grade is 42.5.
[0115] Wherein, the fly ash is secondary fly ash.
[0116] Wherein, the slag is S95 grade slag.
[0117] Wherein, the sand is machine-made sand.
[0118] Wherein, the crushed stone is small pieces of broken rock.
[0119] Wherein, the water reducer is a polycarboxylic acid water reducer.
[0120] The above materials are tested according to the following steps to obtain a floor concrete with excellent anti-shrinkage effect, including the following steps:
[0121] (1) Weigh the materials according to 185 parts of cement, 75 parts of fly ash, 70 parts of slag, 826 parts of sand, 1031 parts of crushed stone, and 7.7 parts of water reducer. Use an electronic balance to weigh the materials. The weighing balance accuracy of the materials is ±0.1g;
[0122] (2) Pour the weighed sand and stone from step (1) into a mixer and stir for 1 min until the mixture is uniform;
[0123] (3) Pour the weighed cement, slag and fly ash in step (1) into a mixer and stir for 1 min until the mixture is uniform;
[0124] (4) pouring the water weighed in step (1) into a blender and stirring;
[0125] (5) adding the water reducing agent weighed in step (1) into the mixer to adjust the working properties of the concrete;
[0126] (6) adding the UEA expansion agent weighed in step (1) into the concrete and stirring until completely dispersed;
[0127] (7) The mixed concrete is placed into a plastic mold and vibrated to remove air bubbles;
[0128] (8) leaving the concrete of step (6) at room temperature for one day and demolding;
[0129] (9) The demoulded test piece is placed in a constant temperature and humidity environment for curing;
[0130] (10) The specimen was placed in a self-made test chamber and polished for 10 min. The dust-free performance was tested by a PM2.5 / PM10 detection device in the test chamber.
[0131] Furthermore, the test box described in step (8) is composed of a sealed test box, a PM2.5 / PM10 detection device and an electric roller brush. The PM2.5 / PM10 detection device is installed on the top of the box, and two electric roller brushes are placed at a height of 40 mm from the bottom of the test box, 15 mm from the side panels of the test box, and run at a speed of 200 r / min during the experiment to simulate the wear and tear of the floor concrete during actual use.
[0132] Example 4 is named C-U1.
[0133] Example 5: The components, mass parts and test methods of the green and low-carbon machine-made sand floor concrete with excellent anti-shrinkage and dust-proof properties involved in this example are the same as those of the blank example, and the test steps are the same as those of Example 1, except that UEA expansion agent is added in an amount of 18.5 parts.
[0134] Example 2 is named C-U2.
[0135] Example 6: The components, mass parts and test methods of the green and low-carbon machine-made sand floor concrete with excellent anti-shrinkage and dust-proof properties involved in this example are the same as those of the blank example, and the test steps are the same as those of Example 1, except that UEA expansion agent is added in an amount of 22.2 parts.
[0136] Example 3 is named C-U3.
[0137] Example 7: The components, mass parts and test methods of the green and low-carbon machine-made sand floor concrete with excellent anti-shrinkage and dust-proof properties involved in this example are the same as those of the blank example, and the test steps are the same as those of Example 4, except that the curing agent is evenly applied in an amount of not less than 35 parts.
[0138] Among them, the curing agent is sodium silicate solution, in which SiO2 accounts for 27.3%, Na2O accounts for 8.54% and the modulus is 3.3.
[0139] Example 7 is named C-U1S.
[0140] Example 8: The components, mass parts and test methods of the green and low-carbon machine-made sand floor concrete with excellent anti-shrinkage and dust-proof properties involved in this example are the same as those of the blank example, and the test steps are the same as those of Example 5, except that the curing agent is evenly applied in an amount of not less than 35 parts.
[0141] Example 8 is named C-U2S.
[0142] Example 9: The components, mass parts and test methods of the green and low-carbon machine-made sand floor concrete with excellent anti-shrinkage and dust-proof properties involved in this example are the same as those of the blank example, and the test steps are the same as those of Example 6, except that the curing agent is evenly applied in an amount of not less than 35 parts.
[0143] Example 8 is named C-U3S.
[0144] Compressive strength test:
[0145] Comparative Example 3: This embodiment relates to a green, low-carbon machine-made sand floor concrete with excellent shrinkage resistance and dustproof performance, comprising the following steps:
[0146] The formula is calculated in parts by weight as follows: (1) 185 parts of cement; (2) 75 parts of fly ash; (3) 70 parts of slag; (4) 826 parts of sand; (5) 1031 parts of crushed stone; and (6) 7.7 parts of water reducing agent.
[0147] Among them, the cement grade is 42.5.
[0148] Wherein, the fly ash is secondary fly ash.
[0149] Wherein, the slag is S95 grade slag.
[0150] Wherein, the sand is machine-made sand.
[0151] Wherein, the crushed stone is small pieces of broken rock.
[0152] Wherein, the water reducer is a polycarboxylic acid water reducer.
[0153] The above materials are tested according to the following steps to obtain a floor concrete with excellent anti-shrinkage effect, including the following steps:
[0154] (1) Weigh the materials according to 185 parts of cement, 75 parts of fly ash, 70 parts of slag, 826 parts of sand, 1031 parts of crushed stone, and 7.7 parts of water reducer. Use an electronic balance to weigh the materials. The weighing balance accuracy of the materials is ±0.1g;
[0155] (2) Pour the weighed sand and stone from step (1) into a mixer and stir for 1 min until the mixture is uniform;
[0156] (3) Pour the weighed cement, slag and fly ash in step (1) into a mixer and stir for 1 min until the mixture is uniform;
[0157] (4) pouring the water weighed in step (1) into a blender and stirring;
[0158] (5) adding the water reducing agent weighed in step (1) into the mixer to adjust the working properties of the concrete;
[0159] (6) The mixed concrete is placed into a plastic mold and vibrated to remove air bubbles;
[0160] (7) leaving the concrete of step (6) at room temperature for one day and demolding;
[0161] (8) The demoulded test pieces were placed in a constant temperature and humidity environment for curing for 28 days;
[0162] (9) The compressive strength of concrete specimens shall be tested according to the "Concrete Strength Test and Assessment Standard" (GB / T 50107-2010).
[0163] Comparative Example 3 was named C-0.
[0164] Embodiment 10: This embodiment relates to a green low-carbon machine-made sand floor concrete with excellent shrinkage resistance and dustproof performance, comprising the following steps:
[0165] The formula is calculated in parts by mass as follows: (1) 185 parts of cement; (2) 75 parts of fly ash; (3) 70 parts of slag; (4) 826 parts of sand; (5) 1031 parts of crushed stone; (6) 7.7 parts of water reducing agent; and (7) 14.8 parts of expansion agent.
[0166] Wherein, the expansion agent is UEA expansion agent, and the main components are aluminum sulfate, aluminum oxide and potassium aluminum sulfate.
[0167] Among them, the cement grade is 42.5.
[0168] Wherein, the fly ash is secondary fly ash.
[0169] Wherein, the slag is S95 grade slag.
[0170] Wherein, the sand is machine-made sand.
[0171] Wherein, the crushed stone is small pieces of broken rock.
[0172] Wherein, the water reducer is a polycarboxylic acid water reducer.
[0173] The above materials are tested according to the following steps to obtain a floor concrete with excellent anti-shrinkage effect, including the following steps:
[0174] (1) Weigh the materials according to 185 parts of cement, 75 parts of fly ash, 70 parts of slag, 826 parts of sand, 1031 parts of crushed stone, and 7.7 parts of water reducer. Use an electronic balance to weigh the materials. The weighing balance accuracy of the materials is ±0.1g;
[0175] (2) Pour the weighed sand and stone from step (1) into a mixer and stir for 1 min until the mixture is uniform;
[0176] (3) Pour the weighed cement, slag and fly ash in step (1) into a mixer and stir for 1 min until the mixture is uniform;
[0177] (4) pouring the water weighed in step (1) into a blender and stirring;
[0178] (5) adding the water reducing agent weighed in step (1) into the mixer to adjust the working properties of the concrete;
[0179] (6) adding the UEA expansion agent weighed in step (1) into the concrete and stirring until completely dispersed;
[0180] (7) The mixed concrete is placed into a plastic mold and vibrated to remove air bubbles;
[0181] (8) leaving the concrete of step (6) at room temperature for one day and demolding;
[0182] (9) The compressive strength of concrete specimens shall be tested according to the "Concrete Strength Test and Assessment Standard" (GB / T 50107-2010).
[0183] Example 10 is named C-U1.
[0184] Example 11: The components, their mass parts and testing methods of the green and low-carbon machine-made sand floor concrete with excellent anti-shrinkage and dust-proof properties involved in this example are the same as those of the blank example, and the testing steps are the same as those of Example 10, except that UEA expansion agent is added in an amount of 18.5 parts.
[0185] Example 11 is named C-U2.
[0186] Example 12: The components, mass parts and test methods of the green and low-carbon machine-made sand floor concrete with excellent anti-shrinkage and dust-proof properties involved in this example are the same as those of the blank example, and the test steps are the same as those of Example 10, except that UEA expansion agent is added in an amount of 22.2 parts.
[0187] Example 12 is named C-U3.
[0188] Example 13: The components, mass parts and test methods of the green and low-carbon machine-made sand floor concrete with excellent anti-shrinkage and dust-proof properties involved in this example are the same as those of the blank example, and the test steps are the same as those of Example 10, except that the curing agent is evenly applied in an amount of not less than 35 parts.
[0189] Among them, the curing agent is sodium silicate solution, in which SiO2 accounts for 27.3%, Na2O accounts for 8.54% and the modulus is 3.3.
[0190] Example 13 is named C-U1S.
[0191] Example 14: The components, mass parts and test methods of the green and low-carbon machine-made sand floor concrete with excellent anti-shrinkage and dust-proof properties involved in this example are the same as those of the blank example, and the test steps are the same as those of Example 11, except that the curing agent is evenly applied in an amount of not less than 35 parts.
[0192] Example 14 is named C-U2S.
[0193] Example 15: The components, mass parts and test methods of the green and low-carbon machine-made sand floor concrete with excellent anti-shrinkage and dust-proof properties involved in this example are the same as those of the blank example, and the test steps are the same as those of Example 12, except that the curing agent is evenly applied in an amount of not less than 35 parts.
[0194] Example 15 is named C-U3S.
[0195] Results and conclusions:
[0196] Depend on Figure 2It can be seen that the drying shrinkage of several groups of concrete increases with the extension of age. Among them, concrete without expansion agent has a large shrinkage degree in a dry environment, and the shrinkage range from 1 to 28 days is 5 to 880 μm. However, with the addition of expansion agent, the drying shrinkage of concrete has been significantly alleviated, and with the increase of the dosage, the drying shrinkage can be improved to a greater extent. For C-U1, with the addition of 8% expansion agent, the drying shrinkage from 1 to 28 days is reduced to 4 to 690 μm. For C-U2, with the addition of 10% expansion agent, the drying shrinkage from 1 to 28 days is reduced to 3 to 490 μm. For C-U3, with the addition of 12% expansion agent, the drying shrinkage from 1 to 28 days is reduced to 2 to 440 μm. Taking the final shrinkage at 28 days as a comparison, the 8% expansion agent reduced the concrete drying shrinkage by about 21.6%, the 12% expansion agent reduced the concrete drying shrinkage by about 44.3%, and the 16% expansion agent reduced the concrete drying shrinkage by about 50%.
[0197] The dust-free performance test results are as follows: Figure 3 As shown. The addition of expansive agent can only improve the dust-free performance of concrete to a small extent. 8% of the expansive agent reduced the dust mass concentration by 10.6%, 10% of the expansive agent reduced the dust mass concentration by 14.6%, and 12% of the expansive agent reduced the dust mass concentration by 19.4%. This may be mainly attributed to the fact that the addition of expansive agent increases the density of concrete to a certain extent, reduces pores and defects, and thus reduces the generation and escape of dust. In addition, the expansive agent can effectively prevent the generation of concrete cracks by generating expansion stress in concrete, thereby reducing the channels for dust escape. But in general, the addition of expansive agent alone still has limited effect on the improvement of concrete dust-free performance. In comparison, on the basis of adding expansive agent, evenly applying curing agent on the surface of concrete can improve the dust-free performance to a greater extent. When 8% of the expansive agent was added to the concrete and the curing agent was applied, C-UIS was obtained, and the dust mass concentration was reduced to 80.2, which was 84.1% lower than that of plain concrete; when 10% of the expansive agent was added to the concrete and the curing agent was applied to the concrete and the dust mass concentration was reduced to 50.8, which was 89.9% lower than that of plain concrete; when 12% of the expansive agent was added to the concrete and the curing agent was applied to the concrete and the dust mass concentration was reduced to 34.8, which was 93.1% lower than that of plain concrete.
[0198] Although the addition of expansive agent can improve the drying shrinkage and dust-free performance of concrete, its addition may affect the normal hydration process of cement to a certain extent, causing a significant decrease in the mechanical properties of concrete such as compressive strength. This patent also observed this situation. The compressive strength of C-U1, C-U2 and C-U3 decreased by 8.5%, 15% and 24.9% respectively compared with plain concrete. However, this strength loss can be compensated by the addition of curing agent, and is even higher than the plain concrete in the control group. The compressive strength of C-U1S and C-U2S increased by 14.5% and 6% compared with plain concrete. Although C-U3S has decreased, its strength is still higher than 30MPa, which still meets the strength grade of C30 concrete.
[0199] Taking the three properties into consideration, it is concluded that C-U3S is the final result of the research and development of this patent, that is, when the expansion agent dosage is 12%, evenly applying no less than 35 parts of curing agent on the surface of the concrete matrix is a green and low-carbon machine-made sand floor concrete.
[0200] In some other embodiments, the data show that: the expansion agent is a UEA expansion agent, the main components of which are aluminum sulfate, aluminum oxide, and potassium aluminum sulfate; the curing agent is a sodium silicate solution, in which SiO2 accounts for 27.3% of its chemical composition, Na2O accounts for 8.54%, and the modulus is 3.3, which has an important influence on the preparation of green and low-carbon machine-made sand floor concrete with excellent anti-shrinkage and dust-proof properties. Hydrophobic modifiers other than the above-mentioned values cannot achieve the technical purpose of the present application of excellent water resistance and material strength.
[0201] The embodiments of the present invention are described in detail above, but the contents described are only preferred embodiments of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A green low-carbon machine-made sand floor concrete and a preparation method thereof, comprising 185 parts of cement, 75 parts of fly ash, 70 parts of slag, 826 parts of machine-made sand, 1031 parts of crushed stone, 7.7 parts of polycarboxylate water reducer, 14.8-22.2 parts of expansion agent and 35-45 parts of curing agent, characterized in that: The expansion agent is UEA expansion agent, and the curing agent is sodium silicate solution.
2. A green and low-carbon machine-made sand floor concrete and a preparation method thereof according to claim 1, characterized in that: The curing agent is a sodium silicate solution, in which SiO2 accounts for 27.3%, Na2O accounts for 8.54% and the modulus is 3.
3.
3. A green and low-carbon machine-made sand floor concrete and a preparation method thereof according to claim 1, characterized in that: The expansion agent is a UEA expansion agent, and the main components of the UEA expansion agent are aluminum sulfate, aluminum oxide, and potassium aluminum sulfate.
4. According to any one of claims 1 to 3, the green and low-carbon machine-made sand floor concrete has a drying shrinkage of 2 to 440 μm from 1 to 28 days.
5. According to any one of claims 1 to 3, the green low-carbon machine-made sand floor concrete, the dust mass concentration generated by grinding the green low-carbon machine-made sand floor concrete is 34.8 mg·m -3 .
6. According to a green and low-carbon machine-made sand floor concrete according to any one of claims 1 to 3, the 28-day compressive strength of the green and low-carbon machine-made sand floor concrete is 34.8 MPa.
7. A green and low-carbon machine-made sand floor concrete and a preparation method thereof according to any one of claims 1 to 6, characterized in that: The steps include: (1) Measure cement, admixtures, sand, stone, water, water reducing agent and expansion agent according to mass fraction; (2) Put the weighed cement, admixture, sand, stone, water and water reducing agent into a mixer, and stir the mixture until it is uniform to obtain a mixture; (3) pouring the expansion agent into the concrete mixture of step (2) during the mixing process, and continuing to mix with a mixer until it is completely uniform; (4) The concrete mixed in step (3) is placed into a mold and vibrated. (5) The concrete of step (4) is placed at room temperature for one day and demoulded. (6) After demoulding, the test block is placed in a constant temperature and humidity environment for curing. (7) Apply the curing agent evenly on the surface of the cured test block to allow the substrate to absorb it. When the substrate surface becomes viscous, spray a small amount of water to promote further penetration of the curing agent. The penetration time should not be less than 10 hours.
8. The green and low-carbon machine-made sand floor concrete and its preparation method according to claim 7 is characterized in that: The curing conditions in step (7) are 20 (±2)° C. and 99% RH.
9. The use of a green and low-carbon machine-made sand floor concrete according to any one of claims 1 to 6, characterized in that: The green and low-carbon machine-made sand floor concrete is used for floor construction.
Citation Information
Patent Citations
Machine-made sand self-leveling concrete
CN102617091A
Concrete ground hardening and polishing process
CN104259944A
Aqueous permeable concrete sealing and curing agent
CN105819894A
Micro expansion concrete
CN107265969A
Low-shrinkage high-strength concrete and preparation method thereof
CN111439971A